MENGUATKAN KEARIFAN LOKAL MENGGUNAKAN PENDEKATAN PARTISIPATIF UNTUK MENGHASILKAN PELESTARIAN LINGKUNGAN HIDUP MASYARAKAT PESISIR DESA NII TANASA KECAMATAN LALONGGASUMEETO KABUPATEN KONAWE - Juhaepa; Megawati Asrul Tawulo; Aryuni Salpiana Jabar; Tanzil; Sarpin; Harnina Ridwan (JOURNAL OF COMMUNITY DEDICATION, 2025)
This study examines the strengthening of local wisdom through a participatory approach to environmental conservation in the coastal community of Nii Tanasa Village. Coastal communities play a key role in ecosystem management, where customary values ​​and traditional practices serve as strong guidelines for pro-environmental behavior. The participatory approach actively engages the community in the planning, implementation, and evaluation of conservation activities, such as mangrove planting, waste management, and fishing monitoring. Survey results indicate a high level of participation, particularly in beach cleanup (78%) and mangrove rehabilitation (68%), as well as a collective awareness supported by adherence to customary rules (72%). Qualitative analysis reveals that collaboration between traditional leaders, fishing groups, and the government strengthens sustainable and inclusive conservation mechanisms. Environmental education strengthens the integration of cultural values ​​into conservation practices, increasing collective awareness and behavior. This approach not only maintains the balance of the coastal ecosystem but also improves socio-economic well-being through ecotourism opportunities and natural resource resilience. The findings confirm that the synergy of local wisdom and active participation is an effective strategy for adaptive and sustainable environmental conservation, while simultaneously strengthening the social capital of coastal communities.